How important is tropospheric humidity for coastal rainfall in the tropics?. Issue 11 (5th June 2016) - Bergemann, Martin; Jakob, Christian
Abstract: Climate models show considerable rainfall biases in coastal tropical areas, where approximately 33% of the overall rainfall received is associated with coastal land‐sea interaction. Building on an algorithm to objectively identify rainfall that is associated with land‐sea interaction we investigate whether the relationship between rainfall in coastal regions and atmospheric humidity differs from that over the open ocean or over inland areas. We combine 3‐hourly satellite estimates of rainfall with humidity estimates from reanalyses and investigate if coastal rainfall reveals the well‐known relationship between area‐averaged precipitation and column‐integrated moisture. We find that rainfall that is associated with coastal land‐sea effects occurs under much drier midtropospheric conditions than that over the ocean and does not exhibit a pronounced critical value of humidity. In addition, the dependence of the amount of rainfall on midtropospheric moisture is significantly weaker when the rainfall is coastally influenced. Key Points: The presence of the coast influences the humidity to rainfall relationship in the tropics Coastally influenced rainfall can occur in drier atmospheres than over the open ocean or over continental land There is no discernible critical humidity value for the pickup of coastal rainfall